A dilute‐and‐shoot liquid chromatography–tandem mass spectrometry method for urinary 18‐hydroxycortisol quantification and its application in establishing reference intervals. Issue 8 (2nd July 2022) - Zhao, Beibei; Bian, Jin; Rao, Menghua; She, Xuhui; Lou, Ying; Cai, Jun; Ma, Wenjun
Abstract: Background: Eighteen‐hydroxycortisol (18‐OHF) is a potential biomarker for differential diagnosis of the two major primary aldosteronism subtypes, aldosterone‐producing adenoma, and idiopathic hyperaldosteronism. Methods: Urine samples were processed, and the 18‐OHF in urine samples were successfully quantified by in‐house established dilute‐and‐shoot liquid chromatography–tandem mass spectrometry (LC–MS/MS) method. Separation was accomplished on a Sigma Ascentis Express C18 column with a gradient mixture of phase (A) 0.2% formic acid in water and phase (B) 0.2% formic acid in methanol at a flow rate of 0.4 ml/min. Mass spectrometric detection was performed in positive electrospray ionization mode via a mass spectrometer. Results: The linearity of urinary 18‐OHF ranged from 4.28 to 8.77 × 10 3 nmol/L, with a lower limit of quantification at 4.28 nmol/L. The intra‐ and inter‐precision were both below 3%. The range of analytical recovery was 97.8%–109.2%. The validated dilute‐and‐shoot LC–MS/MS method was compared with the SPE LC–MS/MS method modified from the one reported in 2013. The results by Passing–Bablok regression analysis and Bland–Altman plotting demonstrated a good agreement between the two methods. The presented method was then applied to establish sex‐specific reference intervals from 62 males and 62 females, respectively. The calculated 2.5%–97.5% reference intervals for 24‐h urinary 18‐OHF were 113–703 nmol/day for males and 71.2–450 nmol/day for females. Conclusion: The presented dilute‐and‐shoot LC–MS/MS method for 18‐OHF quantification showed a good performance in the clinical application. Furthermore, the sex‐specific reference intervals for 24‐h urinary 18‐OHF were first established and quite important for its application in primary aldosteronism subtyping. Abstract : A dilute‐and‐shoot liquid chromatography–tandem mass spectrometry method for 18‐hydroxycortisol quantification in the field of primary aldosteronism subtyping was established and validated in this study. The verified method was then applied to establish sex‐specific reference intervals for 24‐h urinary 18‐hydroxycortisol from 62 males and 62 females, respectively. The calculated 2.5%–97.5% reference intervals for 24‐h urinary 18‐hydroxycortisol were 113–703 nmol/day for males and 71.2–450 nmol/day for females.